Surface Tuning of Solid Oxide Fuel Cell Cathode by Atomic Layer Deposition - Choi, Hyung Jong; Bae, Kiho; Grieshammer, Steffen; Han, Gwon Deok; Park, Suk Won; Kim, Jun Woo; Jang, Dong Young; Koo, Junmo; Son, Ji-Won; Martin, Manfred; Shim, Joon Hyung (WILEY-V C H VERLAG GMBH, 2018)
Atomic layer deposition (ALD) is a powerful tool for nanoscale film deposition. It can uniformly deposit films at a monolayer level even in complex 3D structures, while the deposition temperature is relatively low with its potential scalability. In this work, surface tuning of solid oxide fuel cell (SOFC) cathodes is successfully demonstrated by modifying the surface of La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF) with nanoscale lanthanum strontium cobaltite (LSC) using ALD. The ALD-LSC surface-tuning layer can enhance the charge transfer kinetics at the cathode surface, while the backbone LSCF cathode provides a means for ionic and electronic transport. Microstructural analysis shows that the ALD-LSC on LSCF has excellent step coverage, which is enabled by the conformal characteristic of the ALD process. It is found that the electrochemical performance of SOFCs can be enhanced enormously by surface tuning of the cathodes with nanoscale LSC film corresponding to 1-12 nm. Using density functional theory calculations, the enhanced catalytic activity of the surface-tuned SOFC cathode using ALD-LSC could be confirmed. This result demonstrates the possibility of nanoscale surface tuning of SOFC cathodes by using the ALD process to improve the surface activity.
Keywords: OXYGEN-REDUCTION; EXCHANGE KINETICS; SOFC CATHODES; THIN-FILMS; PERFORMANCE; STABILITY; ENERGY